Influence of halide content on the structure and optical properties of organometal perovskites - Секербaев К.С.; Тaурбaев Е.Т.; Ботaнтaевa Г.Е.; Ермухaмед Д. Д.; Дьяконов, В.; Тимошенко, В.Ю.; Таурбаев, Т.И. (Recent Contributions to Physics, 2016)
Structure and optical properties of thin films of organometal halide perovskites, which were prepared by two-steps method of deposition from solutions, consisted of different content of iodine and bromine were investigated. It is noticed that two-step deposition has an advantages in comparison with one-step deposition. These advantages consist in absence of pores and pinholes, high crystallinity.A change of the forbidden gap of perovskite versus the halide content was analyzed by using the optical absorption data. Regularity of the absorption versus energy of incident radiation is produced.The obtained results give evidences of an enhancement of the excitonic transition for the light absorption near the band gap of the bromide-based perovskite in comparison with the iodine- based one. Possibilities of an application of perovskites with desired halide content for creation of cascade solar cells are discussed.